A dança no louvor e na adoração: o intérprete-criador-adorador e o movimento de improviso - SANTOS, Raí Elicio Gonçalves dos (2018)
This work is to question guiding the process of transformation of the performer creator - worshiper in all its improvisational dance continues walking, reflecting bodily adoration scene nowadays. Addresses the interpreter state of perception in dance assimilation path decisively infecting the body, the scene and worship. The survey reflects the past and flowing in this one caught about dance as an expression of praise and worship that is manifested within the evangelical Christian worship, as well as the scenic practice of improvisation in this emerging do.